DISTAL OCCLUSION AND DENTAL CROWDING: TREATMENT STRATEGY - L.V. Smagliuk; M.I. Dmytrenko (Український стоматологічний альманах, 2020)
Dental anomalies are the leading ones among dental diseases in the period of mixed (79,96%) and permanent (84,33%) dentition. According to the results of our studies, frequency of distal occlusion (up to 40%) and dental crowding (up to 65%) are the largest in structure of orthodontic pathology.